THE IMPORTANCE OF FEEDBACK IN TAXATION LIABILITY RELATIONSHIPS - P. Bortnikov, S. (Gênero & Direito, 2020)
the pertinence of the theme is due to the disputable nature of taxation liability problems in legal science. Despite more than fifty years of research, there is still no common opinion as to its definition, functions, principles, classification criteria and relationship with related legal categories. The lack of legal research of the feedback of the violating entity to the authirised body is worth noting as well. Solving these problems would reveal the nature of tax liability to finally improve performance of this public obligation, law and order. The article explores direct and backward communications in taxation. The key approach or method used here is to reveal the impact of both – the tax liability itself and the institute of liability – on business entities’ and private individuals’ economic activity. The article claims, that bringing to account and entering into a relationship where the violator has to explain and substantiate his actions provides a feedback for the public entity. The purpose of tax liability is defined as that of an instrument of bringing the legal relationship back to the regulated state. The article is of practical use for legislators, judicial and administrative bodies, as well as in scientific research of legal responsibility problems in all branches of law. Conclusions and suggestions of the article amend and develop the provisions of responsibility legislation being of methodic importance for further research in this area both theoretically and practically.